RELAÇÃO ENTRE TRANSTORNOS DE HÁBITOS ORAIS COM AS MALOCLUSÃO DE ANGLE E TIPOS FACIAIS - Rossi, Nelson Jose Carrieri (2009)
The malocclusions are always present in our clinical practice, so it is important to prevent the causes of malocclusion. Disorders habits may appear in different malocclusion of Angle, habits These disorders may be causes of malocclusion and highlight the type of facial pattern. The purpose of this study was to examine the relationship upsets the habits with the Angle malocclusion and facial type. The sample consisted of 398 patients with a mean age of 13 years and 3 months. According to the results we can conclude that: There was no statistically significant association between the type of malocclusion and the type of breastfeeding; There was no statistically significant association between the type of malocclusion and finger sucking or pacifier; There was no statistically significant association between facial type and type of breastfeeding; There was no statistically significant association between facial type and the habit of sucking a pacifier; The association between the time of sucking and facial type, there was a higher frequency of this habit in type dolicofacial; There was no association statistically between the time of the habits and malocclusion; time of sucking a pacifier was in superior brachifacial for dolicofacial.(AU)